Correlation of anteroposterior skeletal and soft tissue cephalometric measurements in Kuantan Malay population: A pilot study - Cheong, Joo Ming; Sivagnanam, Mangaiyarkarasi (2022)
Objective: This study is to determine the correlation of the anteroposterior skeletal and soft tissue cephalometric measurements of the Malaysian Malays.